The Influence of Modern Philosophy on Language Education: An Epistemological Analysis - Muhamad Fuad Hasim; Nelly Sakinah; Nurul Amaliyah; Nur Islamiyah; Emilia Rachmawati (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study investigates the influence of modern philosophical thought on the development of language education by examining its epistemological, ontological, and axiological foundations. Using a qualitative literature review approach, the study analyzes major works of modern philosophy—particularly empiricism, rationalism, critical philosophy, and positivism—and explores their implications for educational theory and language learning. The analysis demonstrates that modern philosophy has significantly shaped language education by redefining the sources of knowledge, the role of experience and reason, and the function of language as a medium for constructing meaning and understanding human experience. The findings reveal that empiricism emphasizes sensory experience as the basis of knowledge acquisition, rationalism highlights the role of reason, Kantian criticism synthesizes both approaches, and positivism reinforces empirical verification and methodological rigor in educational practice. These philosophical perspectives collectively influence how language education conceptualizes learning, knowledge formation, and pedagogical objectives. This study contributes to the theoretical discourse on language education by clarifying the philosophical assumptions underlying modern educational practices and by reinforcing the relevance of philosophical inquiry in strengthening conceptual clarity and critical thinking within language education. Abstrak Studi ini menyelidiki pengaruh pemikiran filosofis modern terhadap perkembangan pendidikan bahasa dengan memeriksa landasan epistemologis, ontologis, dan aksiologisnya. Dengan menggunakan pendekatan tinjauan pustaka kualitatif, studi ini menganalisis karya-karya utama filsafat modern—khususnya empirisme, rasionalisme, filsafat kritis, dan positivisme—dan mengeksplorasi implikasinya terhadap teori pendidikan dan pembelajaran bahasa. Analisis menunjukkan bahwa filsafat modern telah secara signifikan membentuk pendidikan bahasa dengan mendefinisikan ulang sumber pengetahuan, peran pengalaman dan akal, serta fungsi bahasa sebagai media untuk membangun makna dan memahami pengalaman manusia. Temuan menunjukkan bahwa empirisme menekankan pengalaman indrawi sebagai dasar perolehan pengetahuan, rasionalisme menyoroti peran akal, kritik Kantian mensintesis kedua pendekatan tersebut, dan positivisme memperkuat verifikasi empiris dan ketelitian metodologis dalam praktik pendidikan. Perspektif filosofis ini secara kolektif memengaruhi bagaimana pendidikan bahasa mengkonseptualisasikan pembelajaran, pembentukan pengetahuan, dan tujuan pedagogis. Studi ini berkontribusi pada wacana teoretis tentang pendidikan bahasa dengan mengklarifikasi asumsi filosofis yang mendasari praktik pendidikan modern dan dengan memperkuat relevansi penyelidikan filosofis dalam memperkuat kejelasan konseptual dan pemikiran kritis dalam pendidikan bahasa.